LESS new, more preservation: Ideational and typological rethinking of existing buildings - Blumfeld Hanada, Kazu; Schemel, Kirsten; Thesing, Manuel (EAAE Annual Conference Proceedings, 2025)
In the future, the essential and most significant part of architectural work will be the preservation and maintenance, the adaptation and reuse, and the further development or continued transformation of existing spaces. Experts largely agree on this. If we intend to meet the climate targets we have set ourselves, we will only be able to create new spaces to a very limited extent. Even a high recycling rate and a radical shift to renewable and circular building materials cannot change this. To date, very few building regulations and standards in European countries adequately reflect the specific and complex requirements of this field. Likewise, only a few architecture faculties address this crucial future design task in their curricula with the necessary depth and complexity. In architecture — and especially in architectural education — the dialogical examination, alteration, or improvement of an existing building requires more differentiated analysis and, in some cases, alternative design approaches. It also necessitates posing a new set of questions. This EAAE panel therefore addressed the following key topics and presented new methods and examples of best practice: How can design approaches convey the necessary know-how regarding the different forms of historical and ideational relevance — from banal func- tional buildings to listed contemporary heritage — and foster sensitivity to the identity and specificity of an existing building? How can specific design and technical expertise in dealing with physical assets — especially in terms of preservation, repair, and further develop- ment — be taught and integrated in the design process with regard to feasibility? Is there a need for additional specialists, or for specific technical knowledge, tools, or methods? Which intelligent and poetic strategies and specific methods can we apply in our design approach to existing buildings, and how can we, as designers, engage in a dialogue with them?